KEEFEKTIFAN BUKU ENSIKLOPEDIA FAMILI CLUSIACEAE KEBUN RAYA BANUA UNTUK MELATIHKAN KETERAMPILAN BERPIKIR KRITIS MAHASISWA - Fitriani, Atung Diah; Zaini, Muhammad; Irianti, Riya (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2024)
An encyclopedia book is a book that has thorough information that explains concepts and displays important images that are organized systematically and alphabetically. It may be used to exercise critical thinking abilities. The purpose of this study is to describe the validity, practicability, and efficacy of Banua Botanical Garden's encyclopedia of the clusiaceae family. The research development of this encyclopedia uses the Educational Design Research (EDR) research method with Tessmer's formative evaluation design. Expert exam subjects are three lecturers from the Biology Education Study Program at Lambung Mangkurat University, individual test subjects are four Phanerogamae course students, and small group test subjects are four Phanerogamae course students. Details of data are obtained from the instruments of content validity, practicality of content, practicality of expectations, and effectiveness of expectations. The study's findings revealed: 1) the validity of the encyclopedia of valid categories; 2) the practicality of category content and category expectations is extremely excellent; 3) The effectiveness of category expectations is very good for training students' critical thinking skills. The encyclopedia book clusiaceae family of Banua Botanical Garden can be one of the teaching materials that can improve the learning process in the Phanerogamae course because it has attractiveness, is easy to use and effectively trains students' critical thinking skills.